2013
DOI: 10.1007/s00128-012-0931-1
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Organochlorine Pesticide Residue in Fishes from the Densu River Basin, Ghana

Abstract: The study was carried out to determine the levels of organochlorine pesticide residue in five fish species Chrysichthys nigrodigitatus, Hepsetus odoe, Tilapia zilli, Heterotis niloticus and Oreochromis niloticus from the Densu river basin (Weija) in Ghana. The fishes sampled from the Weija fish landing site were selected on the basis of their importance to local human fish consumption. The detectable organochlorine pesticides were γ-Hexachlorocyclohexane (HCH), δ-Hexachlorocyclohexane, aldrin and dieldrin. Oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Deribe et al (2014) discovered Endosalfan, ND–42.5 μg/kg in fish muscle from Lake Hawassa, Ethiopia, which is lower than the current result. In Gana, a study conducted by Kuranchie‐Mensah et al (2013) reported an Endosulfan concentration of 0.01–7.52 μg/kg. Another study in Bénin by Yehouenou et al (2014) noted Endosulfan of 9–215 μg/kg concentration.…”
Section: Results and Discusionmentioning
confidence: 99%
“…Deribe et al (2014) discovered Endosalfan, ND–42.5 μg/kg in fish muscle from Lake Hawassa, Ethiopia, which is lower than the current result. In Gana, a study conducted by Kuranchie‐Mensah et al (2013) reported an Endosulfan concentration of 0.01–7.52 μg/kg. Another study in Bénin by Yehouenou et al (2014) noted Endosulfan of 9–215 μg/kg concentration.…”
Section: Results and Discusionmentioning
confidence: 99%
“…The quality of organochlorine pesticides was assured through the analysis of solvent blanks, procedure blanks and duplicate samples. The method was optimized and validated using spiked together with the internal standard to evaluate the recovery of compounds [19]. The recoveries of internal standards ranged between 87% and 104% for all the organochlorine pesticide.…”
Section: Quality Controlmentioning
confidence: 99%
“…Fish : Although fish from the Densu river basin contained several OCPs, with α-endosulfan predominating, MRLs were not exceeded [48]. A study sampling fish from several lakes in Ghana determined DDTs to have the highest concentration, with the highest level found in a catfish (2,205.50 n g/g lw) (Table 1) [1].…”
Section: Ocp Contamination Of Foods In African Countriesmentioning
confidence: 99%